Annual risk of tuberculous infection in the northern zone of India - Chadha V.K; Vaidyanathan P.S; Jagannatha P.S; Unnikrishnan K.P; Mini P.A (The World Health Organization, 2003)
OBJECTIVE: To estimate the annual risk of infection with tubercle bacilli in the northern zone of India. METHODS: A community-based cross-sectional tuberculin survey was conducted among children aged 1-9 years who lived in a sample of villages and urban blocks of six selected districts in a defined north zone of India. A two-stage cluster sampling method was used to select rural and urban clusters. A total of 48 624 children in 598 clusters were subjected to tuberculin testing with one tuberculin unit (1 TU) of PPD RT23 stabilized with Tween 80. The maximum transverse diameter of induration was measured about 72 hours after the test. FINDINGS: Among the 48 624 test-read children, 22 064 (45.4%) had a bacille Calmette-Guérin (BCG) scar. On the basis of the frequency distribution of tuberculin reaction size among 25 816 children without a BCG scar, the prevalence of infection with tubercle bacilli was estimated as 10.3%. The annual risk of infection was computed as 1.9%. The proportion of infected children was significantly higher in urban than rural areas. CONCLUSION: The high rate of tuberculous infection in the north zone of India suggests the need for further intensification of tuberculosis control efforts on a sustained and long-term basis.